1967
DOI: 10.1063/1.1754921
|View full text |Cite
|
Sign up to set email alerts
|

Time Evolution of Picosecond Optical Pulses

Abstract: A high-speed energy correlation technique has been used to measure the time development of the width of the ultrashort pulses generated by a mode-locked Nd+3 glass laser. The laser was simultaneously Q-switched and mode-locked with a saturable absorber and produced a train of approximately 100 ultrashort pulses. It was found that the initial pulses in the train were of the shortest duration and that the pulse width increased from several picoseconds to about 15 picoseconds over the length of the train. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…;ntensity will become broader and broader. This can account for the pulse width broadening observed by Glenn and Brienza [26] and Richardson [27].…”
Section: Comparison Of Calculations With Experimentsmentioning
confidence: 90%
See 1 more Smart Citation
“…;ntensity will become broader and broader. This can account for the pulse width broadening observed by Glenn and Brienza [26] and Richardson [27].…”
Section: Comparison Of Calculations With Experimentsmentioning
confidence: 90%
“…For example, Glenn and Brienza [26] and, very recently, Richardson [27] reported that pulses in the later part of the train were wider in time duration than those occurring early in the train. Korobkin and others [12] and Duguay and others [l 1] also reported the evolution of the spectral structure of the pulse in the train.…”
Section: Temporal Development Of the Spectrummentioning
confidence: 97%
“…In addition, it is known that the temporal and spectral properties of different pulses within a single pulse train may vary considerably ( 1,2 ). For these reasons and considerations involving the subsequent amplification stages, we always utilized single uulses, the selection of which is achieved by a Pockels cell between crossed polarizers( ) (Figure 1, #4).…”
Section: Picosecond Pulse Selection and Characterizationmentioning
confidence: 99%
“…1 ,2 Tungsten, in the form of an incandescent filament, has been reported to exhibit electrotransport by Johnson 3 in 1938 and more recently by O'Boyle. 4 Theories of the electrotransport phenomenon have been reviewed and compared adequately by Verhoeven. 5 This paper shows an example of electrotransport of tungsten on which the life.…”
Section: Introductionmentioning
confidence: 99%